Conditions Influencing Mould Growth for Effective Prevention of Wood Deterioration Indoors - Edgars Kuka; Dace Cirule; Ingeborga Andersone; Bruno Andersons; Velta Fridrihsone (Applied Sciences, 2022)
Effective prevention of mould growth indoors is still an important topic considering that mould growth is frequently observed in buildings, it causes serious health hazards and can irreversibly damage infected objects. Several studies have been conducted and mould growth models developed. Despite that, some potentially important aspects such as water damage and spore contamination have received only little attention. The objective of the present study was to investigate the effect of the initial moisture content of wood and spore contamination on mould development indoors. The mould tests were performed in constant temperature (10, 20 and 30 °C) and relative humidity (91% and 97%) conditions. The results show that wetting of wood specimens prior to the test significantly accelerates mould growth at a temperature of 10 °C. For the other temperatures, the effect was insignificant. Similar results were obtained for the test involving dry (conditioned at RH 50%) and conditioned specimens (RH 91% or RH 97%). The results regarding initial spore contamination show that significantly longer periods are required for mould to develop without spore contamination at 10 °C and 20 °C, while at 30 °C the effect is relatively small.